2408. Delayed Appropriate Antimicrobial Therapy Does Not Affect the Clinical Outcome of Patients With Acute Pyelonephritis by Extended-Spectrum β-Lactamase-Producing Enterobacteriaceae. (26th November 2018) - Kim, Si-Ho; Oh, Suhyun; Jang, Sukbin; Mun, Seokjun; Huh, Kyungmin; Cho, Sun Young; Kang, Cheol-In; Chung, Doo Ryun; Peck, Kyong Ran
Abstract: Background: Extended spectrum β-lactamase-producing Enterobacteriaceae (ESBL-PE) is related to inappropriate empirical therapy for acute pyelonephritis. The aim of this study was to investigate whether the delay in appropriate antimicrobial therapy of APN caused by ESBL-PE was associated with patient`s poor outcome or not. Methods: A retrospective cohort study was performed at a tertiary-care hospital from January 2014 through December 2016. Patients who had APN caused by ESBL-PEs and were treated with appropriate definite antibiotics for at least 7 days were enrolled. The delay in appropriates antimicrobial therapy was defined as patients who had received appropriate antibiotics 48 hour or later after diagnosis of APN. Primary endpoint was treatment failure defined as clinical and/or microbiological failure. Secondary endpoint was length of hospital stay and recurrence of febrile urinary tract infection by ESBL-EP within 1-year. The propensity score matching and multivariable Cox proportional hazard modeling were used to adjust heterogeneity of each group. Results: A total of 175 eligible cases were collected. Escherichia coli (144/175, 82.3%) was the most common pathogen, followed by Klebsiella pneumonia (29/175, 16.5%). 59 (34%) patients received delayed appropriate antibiotics (delayed group) and 116 (66%) patients received appropriate initial empirical antibiotics (appropriate group). Treatment failure was observed in 5 (8.4%) patients and 9 (7.8%) patients in each group. After matching, the risk of treatment failure was similar between the both groups (adjusted odd ratio [aOR] 1.05; 95% confidential index [CI] 0.26–4.15). Mean days of hospitalization length was similar (10.8 days in delayed group vs. 11.1 days in appropriate group; P = 0.717), and recurrence rates was also similar between the both groups (adjusted HR [aHR] 0.92; 95% CI 0.43–2.00, Figure 1). Conclusion: The delay in appropriate antimicrobial therapy did not affect the clinical outcome of patients if they were properly treated thereafter. This suggests that prescription of a broad-spectrum antibiotics was not needed as initial empirical antibiotics for the treatment of APN with a potential risk of EBSL-PE. Disclosures: All authors: No reported disclosures.